2007
DOI: 10.1007/s12011-007-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-dose Sodium Selenite Therapy on Bcl-2 Expression in Adult Non-Hodgkin’s Lymphoma Patients: Correlation with Response and Survival

Abstract: The present study was undertaken to explore the effect of administration of high doses of sodium selenite on the expression of Bcl-2 in patients with non-Hodgkin's lymphoma (NHL). Fifty patients with newly diagnosed NHL were randomly divided into two groups. Group A-I received standard chemotherapy whereas group A-II received adjuvant sodium selenite 0.2 mg kg-1 day-1 for 30 days in addition to chemotherapy. Enzyme-linked immunosorbent assay was used to assess Bcl-2 at the time of diagnosis and after therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…A small clinical randomized study in patients with non-Hodgkin's lymphoma showed that Se supplementation during chemotherapy increases the percentage of cases with a reduction of lymphadenopathy, and decreases splenic size and bone marrow infiltration [15]. Further prospective clinical trials showed that Se can reduce toxicities of chemotherapy in patients with solid tumors and hematological malignancies [15,16,17,18,19,20]. …”
mentioning
confidence: 99%
“…A small clinical randomized study in patients with non-Hodgkin's lymphoma showed that Se supplementation during chemotherapy increases the percentage of cases with a reduction of lymphadenopathy, and decreases splenic size and bone marrow infiltration [15]. Further prospective clinical trials showed that Se can reduce toxicities of chemotherapy in patients with solid tumors and hematological malignancies [15,16,17,18,19,20]. …”
mentioning
confidence: 99%
“…Other studies showed that Se enhances apoptosis via caspase-dependent mode [25]. Recently, Asfour and coworkers demonstrated that adjuvant Se therapy in non-Hodgkin lymphoma patients improves response to therapy, supports the immune system, and has a positive influence on patients' survival [16,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Asfour et al [16] concluded that Na 2 SeO 3 administration acts as a cytoprotective agent, alleviating the immunosuppressive effects of cytotoxic chemotherapy.…”
mentioning
confidence: 99%
“…In the same trial, slowing of PSA velocity was also observed, and one patient had >50% reduction in serum PSA. Another clinical trial adding SS 200 μg/kg/day (equivalent to 14,000 μg/day in a 70-kg adult) to chemotherapy in lymphoma patients reported less toxicity with combination therapy than with chemotherapy alone, including infections and reduction in cardiac function (27).…”
Section: Selenium Compounds -Metabolism Pharmacology and Toxicitymentioning
confidence: 99%
“…Asfour et al reported a trial randomising 50 patients with non-Hodgkin lymphoma to either very high doses of SS (200 μg/kg/day) with cyclophosphamide, vincristine, doxorubicin and prednisone chemotherapy or chemotherapy alone (27). A significantly greater tumour response rate was observed in the Se group than controls (60% vs. 40% respectively), with correspondingly lower levels of the oncogene B-cell lymphoma 2 (BCL2) in bone marrow aspirates in Se-treated patients compared to controls.…”
Section: Antitumour Efficacymentioning
confidence: 99%